Endothelial Nitric Oxide Synthase Is Present in Dendritic Spines of Neurons in Primary Cultures - Caviedes, Ariel; Varas-Godoy, Manuel; Lafourcade, Carlos; Sandoval, Soledad; Bravo-Alegria, Javiera; Kaehne, Thilo; Massmann, Angela; Figueroa, Jorge P.; Nualart, Francisco; Wyneken, Ursula (Frontiers in Cellular Neuroscience, 2017)
Nitric oxide exerts important regulatory functions in various brain processes. Its synthesis in neurons has been most commonly ascribed to the neuronal nitric oxide synthase (nNOS) isoform. However, the endothelial isoform (eNOS), which is significantly associated with caveolae in different cell types, has been implicated in synaptic plasticity and is enriched in the dendrites of CA1 hippocampal neurons. Using high resolution microscopy and co-distribution analysis of eNOS with synaptic and raft proteins, we now show for the first time in primary cortical and hippocampal neuronal cultures, virtually devoid of endothelial cells, that eNOS is present in neurons and is localized in dendritic spines. Moreover, eNOS is present in a postsynaptic density-enriched biochemical fraction isolated from these neuronal cultures. In addition, qPCR analysis reveals that both the nNOS as well as the eNOS transcripts are present in neuronal cultures. Moreover, eNOS inhibition in cortical cells has a negative impact on cell survival after excitotoxic stimulation with N-methyl-D-aspartate (NMDA). Consistent with previous results that indicated nitric oxide production in response to the neurotrophin BDNF, we could detect eNOS in immunoprecipitates of the BDNF receptor TrkB while nNOS could not be detected. Taken together, our results show that eNOS is located at excitatory synapses where it could represent a source for NO production and thus, the contribution of eNOS-derived nitric oxide to the regulation of neuronal survival and function deserves further investigations.